Importance of waste stabilization ponds and wastewater irrigation in the generation of vector mosquitoes in Pakistan - Mukhtar, M.; Ensink, J.; Hoek, W. van der; Amerasinghe, Felix P.; Konradsen, Flemming (2006)
The objective of the current study was to investigate the role of waste stabilization ponds (WSP) and wastewater-irrigated sites for the production of mosquitoes of medical importance. Mosquito larvae were collected fortnightly from July 2001 to June 2002 in Faisalabad, Pakistan. In total, 3,132 water samples from WSP and irrigated areas yielded 606,053 Culex larvae of ?ve species. In addition, 107,113 anophelines, representing eight species were collected. Anopheles subpictus (Grassi) and Culex mosquitoes, especially Culex quinquefasciatus (Say) and Culex tritaeniorhynchus (Giles), showed an overwhelming preference for anaerobic ponds, which receive untreated wastewater. Facultative ponds generated lower numbers of both Anopheles and Culex mosquitoes, whereas the last ponds in the series, the maturation ponds, were the least productive for both mosquito genera. An. subpictus and Anopheles stephensi (Liston) were the dominant Anopheles species in wastewaterirrigated sites, with Anopheles culicifacies (Giles) recorded in low numbers. This was also the pattern in nearby sites, irrigated with river water. Among the Culex species, Cx. tritaeniorhynchus was by far the most frequently recorded in both wastewater- and river water-irrigated sites with Cx. quinquefasciatus as the second most abundant species but restricted to wastewater-irrigated areas. Univariate logistic regression analysis showed that presence of An. subpictus and Culex mosquitoes was signi?cantly associated with emergent grass vegetation and low salinity. Regular removal of emergent grass along the margins of the anaerobic ponds and changes in the concrete design of the ponds are likely to reduce the mosquito production, especially of Culex species.